2020
DOI: 10.23947/2334-8496-2020-8-si-79-91
|View full text |Cite
|
Sign up to set email alerts
|

Creativity Formation in the Context of Social and Psychological Adaptation of Preschoolers Aged 5-6 Years

Abstract: The aim of the research is to analyze the creativity manifestation in the early stages of ontogenesis; to verify the relationship between creative abilities and social adaptation of preschoolers. The importance of the topic under consideration is determined by the fact that preschoolers’ childhood is the main sensitive period for the formation of creativity as the person’s adaptive re-source. The deficiency of development during this period cannot be compensated later. The examination of the creative abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 17 publications
0
4
0
12
Order By: Relevance
“…A large part of a child's personality is developed during their pre-school educational years. Scholars Laryssa V. Zdanevych, et al's research found that pre-schoolers were most sensitive to creative potential within the development of their personalities (Zdanevych et al, 2020). Children naturally are curious of their surrounding environment, in awe of discoveries, experiment, use their imaginations and daydream (Zdanevych et al, 2020).…”
Section: The Creative Personalitymentioning
confidence: 99%
See 2 more Smart Citations
“…A large part of a child's personality is developed during their pre-school educational years. Scholars Laryssa V. Zdanevych, et al's research found that pre-schoolers were most sensitive to creative potential within the development of their personalities (Zdanevych et al, 2020). Children naturally are curious of their surrounding environment, in awe of discoveries, experiment, use their imaginations and daydream (Zdanevych et al, 2020).…”
Section: The Creative Personalitymentioning
confidence: 99%
“…Scholars Laryssa V. Zdanevych, et al's research found that pre-schoolers were most sensitive to creative potential within the development of their personalities (Zdanevych et al, 2020). Children naturally are curious of their surrounding environment, in awe of discoveries, experiment, use their imaginations and daydream (Zdanevych et al, 2020). Scholars Laryssa V. Zdanevych et al describes a creative personality as being talented with "emotional impertinence and expressed weirdness of behavior."…”
Section: The Creative Personalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Our comparison of academic performance and switch costs between groups of schoolchildren who acquired two concepts with or without switching showed remote benefit of learning with switching accompanied by greater cognitive effort (to be published after complete data analysis). Therefore, of importance is the "management" of multitasking that would increase the effectiveness of learning using segmentation of individual learning episodes, grouping of tasks by importance, and other tools of reorganization of experience (Stavtseva, 2014), and would possibly mediate the developing creative abilities (see Markina and Vladimirov, 2019;Zdanevych et al, 2020).…”
Section: Task Switching and Applied Research In Educationmentioning
confidence: 99%
“…Radošuma attīstību būtu jāiekļauj pirmskolas izglītības iestāžu programmās, lai šīs prasmes tiktu attīstītas jau agrīnā vecumā. (Zdanevych, et al, 2020).…”
Section: Introductionunclassified